"Centering": a fundamental instrument for teaching balance in competitive adolescents - Fogliata, A.; Borghini, R.; Ambretti, A. (Journal of Physical Education and Sport, 2023)
For many years, there has been a debate regarding the role of intra-abdominal pressure (IAP) in supporting the vertebral column, particularly in the lumbar region. The role of IAP is particularly evident during physical activities that require complex movements and rapid jumps (Paoli et al., 2010). The hypothesis that IAP relieves the compressive load on the lumbar vertebrae by better distributing the force vectors during physical activities was first proposed in 1923 by Keith and subsequently discussed by Bartelink (Bartelink, 1957). This hypothesis was later confirmed by Morris et al. in 1961 using a mechanical model. The authors demonstrated that a voluntary increase in IAP alleviates lumbar compression, both directly and indirectly, by inducing spinal extension, causing flattening in the cup-shaped form of the thoracic diaphragm muscle (Morris et al., 1961). Other authors have confirmed the important role of IAP in coordinating the activity of trunk muscles (Stokes et al., 2010; Madle et al., 2022), and its indirect contribution to respiration has been expanded upon and studied (Hodges, 2000). These aspects are crucial for achieving good performance in sports involving acceleration and jumping (Gennaro et al., 2019; Bitnar et al., 2015; Hwang et al., 2021). Therefore, it is possible to activate the components of the trunk stabilization system using its muscles by increasing IAP, which is associated with voluntary use of the thoracic diaphragm muscles (Stokes et al., 2011). Performance improvement has also been demonstrated using "Centering" (Debernardi, 2008). "Centering" (CENT) is the proportional utilization of IAP depending on forces experienced due to the acceleration during sports movements. CENT improves the execution of technical gestures and their learning (Fogliata et al., 2022). Owing to the importance of CENT in the stabilization and protection system, the aim of this study was to verify the possible effects of CENT on balance and stabilization dynamics (Malwanage et al., 2022) and to study possible differences in balance between adolescents with and without CENT. Furthermore, the Stork test was employed to identify possible changes in balance parameters in adolescents with and without CENT (Condon, 2014).